Dehydration of Fructose into 5-Hydroxymethylfurfural Catalyzed by Phosphorylated Activated Carbon Catalyst - Yang, Li; Wang, Miaofeng; Yan, Xiaopei; Wang, Yilan; Xia, Haian (Asian Journal of Chemistry, 2015)
Surface functionalized activated carbon catalysts with phosphate group were synthesized and used to catalyze dehydration of fructose into 5-hydroxymethylfurfural. The surface oxygen-containing functional groups of phosphorylated activated carbon were characterized and analyzed by XPS, infrared spectroscopy and Boehm titration techniques. The catalysts exhibit high dehydration activity of fructose but low 5-hydroxymethylfurfural selectivity using water as the solvent. Organic solvent can effectively improve the 5-hydroxymethylfurfural selectivity and yield. The highest 5-hydroxymethylfurfural yield of 66.6 % was achieved using DMSO as the solvent at 160 °C for 30 min. It was found that the amount of phosphate group is correlated with the fructose conversion, but higher concentration of phosphate group leads to the decrease of 5-hydroxymethylfurfural selectivity.